ANALISIS KUALITATIF DOKUMEN REKAM MEDIS RAWAT INAP PADA PASIEN TUBERKULOSIS PARU - Novita Nuraini; Demiawan Rachmatta Putro Mudiono; Mitha Audia Rachma (Politeknik Negeri Jember, 2020)
Qualitative analysis is a review of filling medical records relating to the consistency of the contents of the medicalrecord. A good medical record must contain complete medical records. This study aims to analyze qualitativeinpatient Medical Record Documents (DRM) in pulmonary tuberculosis patients in Tongas Probolinggo RegionalHospital in the first quarter of 2017. This research type is descriptive with a qualitative approach with datacollection techniques of observation and interviews. The results of this study are that there are still documentson pulmonary tuberculosis medical records at Tongas Probolinggo Regional Hospital which are still incompleteand inaccurate. One of them is in the administrative qualitative analysis, which is the incomplete patient addresswriting100%, because nurses pay less attention and remind patients / guardians in filling out informed consentsheets. In addition, medical staff did not apply 100% of the writing of the tuberculosis standard abbreviationcontained in the SOP of the Tongas Hospital Standard Standard, because there was still a lack of socializationfrom the RM unit to medical personnel related to the use of the tuberculosis standard abbreviation. In aqualitative medical analysis, there were no X-ray examination results on patients who had X-ray examinationsas many as 19 documents, because in Tongas Regional Hospital did not have an examination result sheet, sothe results of the examination were not written in the DRM. So the quality of DRM in patients with pulmonarytuberculosis both administratively and medically is still not good. It is better if the accuracy and discipline ofmedical staff are needed in filling DRM